1985
DOI: 10.1530/jrf.0.0730497
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of palmitate in cultured rat Sertoli cells

Abstract: Summary. Isolated rat Sertoli cells were incubated in the presence of [1-14C]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 16 publications
1
31
0
Order By: Relevance
“…An indication that lipids may be a more important energy substrate than glucose for Sertoli cells was provided by Jutte et al (2) who showed that Sertoli cells oxidize palmitate in a concentration-dependent manner and that the addition of glucose to the incubation system does not change palmitate oxidation but causes a 9-fold increase in palmitate esterification to TG, probably due to an increase in glycerol-3-phosphate levels. Fisher and Coniglio (21) demonstrated that the amount of radioactivity in the TG of Sertoli cells was constant between 24 and 48 h but was decreased in PL, suggesting a higher FA turnover in PL than in TG.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An indication that lipids may be a more important energy substrate than glucose for Sertoli cells was provided by Jutte et al (2) who showed that Sertoli cells oxidize palmitate in a concentration-dependent manner and that the addition of glucose to the incubation system does not change palmitate oxidation but causes a 9-fold increase in palmitate esterification to TG, probably due to an increase in glycerol-3-phosphate levels. Fisher and Coniglio (21) demonstrated that the amount of radioactivity in the TG of Sertoli cells was constant between 24 and 48 h but was decreased in PL, suggesting a higher FA turnover in PL than in TG.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolism of [ 14 C]palmitic acid in primary cultures of rat Sertoli cells isolated from testes of 19-day old rats has been reported (2). The oxidation of palmitate was concentration dependent.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cultured rat SCs rely in fatty acids oxidation to sustain their energetic needs [67]. Moreover, they phagocytize and degrade apoptotic spermatogenic cells and residual bodies to form lipids that can be then re-used to produce ATP during spermatogenesis [68].…”
Section: Metabolic Cooperation In Testis Is Piv-otal For Spermatogenesismentioning
confidence: 99%